2016
DOI: 10.1007/s10689-016-9930-4
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with cancer worries in individuals participating in annual pancreatic cancer surveillance

Abstract: It is important to adequately and timely identify individuals with cancer worries amongst participants in a pancreatic ductal adenocarcinoma (PDAC) surveillance program, because they could benefit from psychosocial support to decrease distress. Therefore, the aim of this study was to assess both psychosocial and clinical factors associated with cancer worries. High-risk individuals participating in PDAC-surveillance were invited to annually complete a cancer worry scale (CWS) questionnaire which was sent after… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(35 citation statements)
references
References 35 publications
1
33
1
Order By: Relevance
“…Previous studies in CRC 20 and prostate cancer survivors 32 both showed that one in four had high levels of worry of cancer recurrence (CWS ≥ 14 in eight‐item CWS), with a median of 5.1 and 7.5 years after surgery, respectively 20 . Although the CWS has been validated for cancer survivors, it has also been used to measure worry about the risk of developing cancer among participants in a cancer surveillance program 33 . The cutoff point ≥10, based on a Dutch validation study in cancer patients and survivors, has led to our conclusion that there was a high level (17%) of cancer‐specific worry up to 6 months in patients with no malignant lesions.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies in CRC 20 and prostate cancer survivors 32 both showed that one in four had high levels of worry of cancer recurrence (CWS ≥ 14 in eight‐item CWS), with a median of 5.1 and 7.5 years after surgery, respectively 20 . Although the CWS has been validated for cancer survivors, it has also been used to measure worry about the risk of developing cancer among participants in a cancer surveillance program 33 . The cutoff point ≥10, based on a Dutch validation study in cancer patients and survivors, has led to our conclusion that there was a high level (17%) of cancer‐specific worry up to 6 months in patients with no malignant lesions.…”
Section: Discussionmentioning
confidence: 99%
“…18,19 In addition, the CWS’s clinical cutoff scores are empirically based. In its development, the CWS assessed sensitivity, specificity, and positive and negative predictive values at each cutoff point against 2 items of the Cancer Acceptance Scale.…”
Section: Methodsmentioning
confidence: 99%
“…Overall, 21% of the sample reported sustained moderate to elevated distress . The same research team reports in a similar study that 33% of individuals undergoing pancreatic cancer surveillance experienced cancer worry, especially those with a family history of early‐onset pancreatic cancer . Two other prospective studies have been completed in a sample of unaffected individuals with high pancreatic cancer risk.…”
Section: Introductionmentioning
confidence: 96%
“…6 The same research team reports in a similar study that 33% of individuals undergoing pancreatic cancer surveillance experienced cancer worry, especially those with a family history of early-onset pancreatic cancer. 7 Two other prospective studies have been completed in a sample of unaffected individuals with high pancreatic cancer risk. In these 2 studies, distress, cancer worry, and risk perception were measured 3 months 8 and 1 year following genetic counseling and screening.…”
Section: Introductionmentioning
confidence: 99%